2021
DOI: 10.3390/jcm10071495
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Silver-Releasing Foam Dressings on Diabetic Foot Ulcer Healing

Abstract: Diabetic foot ulcers (DFUs) are a serious complication in diabetic patients and lead to high morbidity and mortality. Numerous dressings have been developed to facilitate wound healing of DFUs. This study investigated the wound healing efficacy of silver-releasing foam dressings versus silver-containing cream in managing outpatients with DFUs. Sixty patients with Wagner Grade 1 to 2 DFUs were recruited. The treatment group received silver-releasing foam dressing (Biatain® Ag Non-Adhesive Foam dressing; Colopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Similar results have been reported in a study that involved patients with burn wounds, where silver foam dressing relieved the patients of pain through infection control and rapid wound healing 36 . A recent study involving silver‐releasing foam dressings versus silver‐containing cream in managing outpatients with DFUs also found that silver‐dressing foam is effective, especially during the early stages of wound management 37 …”
Section: Results and Analysissupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results have been reported in a study that involved patients with burn wounds, where silver foam dressing relieved the patients of pain through infection control and rapid wound healing 36 . A recent study involving silver‐releasing foam dressings versus silver‐containing cream in managing outpatients with DFUs also found that silver‐dressing foam is effective, especially during the early stages of wound management 37 …”
Section: Results and Analysissupporting
confidence: 74%
“…36 A recent study involving silver-releasing foam dressings versus silvercontaining cream in managing outpatients with DFUs also found that silver-dressing foam is effective, especially during the early stages of wound management. 37 A combination of silver with magnesium in Ag-Mg-thermoplastic polyurethane (Ag-Mg-TPU) composite material has correspondingly been shown to increase both the amount and rate of silver ion released from the composite, and with an increased antimicrobial effect. 38 More recent advances in wound management technologies point to a brighter future for the healthcare sector and patients.…”
Section: Dressing Materialsmentioning
confidence: 99%
“…These dressings with good water vapor permeability are utilized in the treatment of ulcers of the lower limbs, pressure ulcers (stage I–IV), skin transplants, and mild burns (stage I–II) [ 133 ]. The commercially available dressings based on polyurethane include Allevyn™, Askina Foam™, Tielle™, and Lyofoam™ [ 90 ]. However, unsuitability for dry wounds and frequent changes limits the effectiveness of such dressings.…”
Section: Wound Dressings and Recent Advancementsmentioning
confidence: 99%
“…Some studies have reported that more complex skin dressings, including sponges, thin films, foams, hydrocolloids, silver dressings, and iodine dressings, are used as substitutes. In addition, a number of mixed dressings with antibacterial properties such as silver ion-containing foams and silver-containing activated carbon fibers are applied in the treatment of diabetic wounds [ 29 , 30 ]. However, these dressings still have some limitations.…”
Section: Wound Healingmentioning
confidence: 99%